2013
DOI: 10.1093/mp/sst012
|View full text |Cite
|
Sign up to set email alerts
|

NAC Transcription Factor ORE1 and Senescence-Induced BIFUNCTIONAL NUCLEASE1 (BFN1) Constitute a Regulatory Cascade in Arabidopsis

Abstract: Senescence is a highly regulated process that involves the action of a large number of transcription factors. The NAC transcription factor ORE1 (ANAC092) has recently been shown to play a critical role in positively controlling senescence in Arabidopsis thaliana; however, no direct target gene through which it exerts its molecular function has been identified previously. Here, we report that BIFUNCTIONAL NUCLEASE1 (BFN1), a well-known senescence-enhanced gene, is directly regulated by ORE1. We detected elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
148
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(151 citation statements)
references
References 44 publications
(97 reference statements)
2
148
0
1
Order By: Relevance
“…Collectively, these molecular and genetic studies bring about a wholly connected signaling cascade of EIN2-EIN3-miR164-NAC2, which we refer to as the NAC2 pathway. Several studies have identified a subset of downstream genes of NAC2 transcription factor in the control of senescence (Balazadeh et al, 2010), such as BIFUNCTIONAL NUCLEASE1, SAG29/SWEET15, and SINA1 (Matallana- Ramirez et al, 2013). Together with our findings, it is thus possible to assemble the signaling pathways and molecular network that modulate the intricate processes of leaf senescence.…”
Section: The Emergence Of a Senescence Signaling Cascade Involving Eisupporting
confidence: 77%
“…Collectively, these molecular and genetic studies bring about a wholly connected signaling cascade of EIN2-EIN3-miR164-NAC2, which we refer to as the NAC2 pathway. Several studies have identified a subset of downstream genes of NAC2 transcription factor in the control of senescence (Balazadeh et al, 2010), such as BIFUNCTIONAL NUCLEASE1, SAG29/SWEET15, and SINA1 (Matallana- Ramirez et al, 2013). Together with our findings, it is thus possible to assemble the signaling pathways and molecular network that modulate the intricate processes of leaf senescence.…”
Section: The Emergence Of a Senescence Signaling Cascade Involving Eisupporting
confidence: 77%
“…After selection, 34 clones with high binding activity were sequenced. The sequence alignment of these clones and base substitution or insertion analysis, together with knowledge about the allowable spacer length of homologous NAC protein-binding sites (Xue et al, 2006;Matallana-Ramirez et al, 2013), revealed two types of bipartite sequences, namely VDHVnnYRR (5-6n)YACGnMWSK (BS1) and RRWnnCGTR(5-6n) DACGTMWHD (BS2), as ATAF1-binding sites (underlined nucleotides represent 100% conservation in the sequenced clones; Supplemental Table S2). Recently, Jensen et al (2013) used protein-binding microarrays covering all possible 8-mer DNA sequences and reported the monopartite 6-mer motifs TT[A,C,G]CGT and T(A,C,G)CGT(A,G) as the binding sites of ATAF1.…”
Section: Identification Of the Consensus Target Sequence Of Ataf1mentioning
confidence: 99%
“…In Arabidopsis, positive senescence regulators include ORESARA1 (ORE1; also called ARABIDOPSIS NAC092 [ANAC092] or AtNAC2; Kim et al, 2009;Balazadeh et al, 2010a;Rauf et al, 2013a), ORESARA1 SISTER1 (ORS1; ANAC059; Balazadeh et al, 2011), AtNAP (for Arabidopsis NAC-LIKE, ACTIVATED BY APETALA3/ PISTILLATA; ANAC029; Guo and Gan, 2006), and ANAC016 , while negative regulators include JUNGBRUNNEN1 (JUB1; ANAC042; Wu et al, 2012) and VND-INTERACTING2 (ANAC083; Yang et al, 2011). Furthermore, downstream target genes of some of the senescence-regulated NAC TFs have been reported, including BIFUNCTIONAL NUCLEASE I (BFN1), RIBONUCLEASE3, SEVEN-IN-ABSENTIA1 (SINA1), and SENESCENCE-ASSOCIATED GENE29 (SAG29; SWEET15) for ORE1 (Balazadeh et al, 2010a;Matallana-Ramirez et al, 2013;Rauf et al, 2013a), DEHYDRATION-RESPONSIVE ELEMENT BINDING PROTEIN2 for JUB1 (Wu et al, 2012), and SAG113 for AtNAP (Guo and Gan, 2006). These studies reveal first insights into the complex regulatory networks underlying plant senescence.…”
mentioning
confidence: 99%
“…Several stay-green mutants have been isolated, of which many are transcription factor mutants (Kusaba et al, 2013;Penfold and Buchanan-Wollaston, 2014). For example, the NAC (for no apical meristem [NAM], Arabidopsis transcription activation factor [ATAF1-2], and cup-shaped cotyledon [CUC2]) transcription factor ORESARA1 (ORE1) is regulated at the transcriptional and posttranscriptional levels and promotes leaf senescence through transcriptional modulation of target genes, such as BIFUNCTIONAL NUCLEASE1 and GOLDEN2-LIKE1/2 (Kim et al, 2009;Matallana-Ramirez et al, 2013;Rauf et al, 2013). As mentioned previously, plant hormones play an important role in regulating leaf senescence.…”
mentioning
confidence: 99%